Parenting in a digital age: A review of parents' role in preventing adolescent cyberbullying. (July 2017) - Elsaesser, Caitlin; Russell, Beth; Ohannessian, Christine McCauley; Patton, Desmond
Abstract: While parents have a critical influence on reducing adolescent risk taking, adolescents' access to online spaces presents significant and novel challenges to parents' ability to reduce their youth's involvement in cyberbullying. The present study reviews the existing literature on parents' influence (i.e., parental warmth and parental monitoring) on adolescent cyberbullying, both as victims and perpetrators. 23 mostly cross sectional articles were identified for this review. Findings indicate that parental warmth is consistently associated with lower cyberbullying, both as victims and perpetrators. For parental monitoring, strategies that are focused on parental control, such as restricting the Internet, appear to be only weakly related to youth's involvement in cyberbullying victimization and perpetration. In contrast, strategies that are more collaborative with in nature (e.g., evaluative mediation and co-use) are more closely connected to cyberbullying victimization and perpetration, although evidence suggests that the effectiveness of these practices varies by sex and ethnicity. Results underscore the need for parents to provide emotional warmth that might support adolescent's disclosure of online activity. Implications for practice and future research are reviewed. Highlights: We review literature on parents' influence on adolescent cyberbullying Parental warmth is associated with lower cyberbullying, both as victims and perpetrators The internet mediation strategy of parental control is only weakly related to cyberbullying victimization and perpetration. Control strategies collaborative in nature (e.g., co-use) are linked to lower cyberbullying victimization and perpetration